Endometriosis of the colon. Issue 667 (May 1981) - Michowitz, M.; Lazarovici, I.; Hammar, B.; Solowiejczyk, M.
Abstract : A case of endometriosis of the colon is presented. The incidence, symptomatology and treatment are discussed.